Green Atmospherics as Nature-Based Solutions and Patient Responses and Behaviors in Healthcare Establishments From Romania. (March 2023) - Untaru, Elena-Nicoleta; Han, Heesup; Bălăşescu, Simona; Kim, Bona; Ariza-Montes, Antonio
The present study aims to evaluate a conceptual framework that explains patients' attachment to a healthcare establishment by considering the effect of a natural/green environment as nature-based solutions (NBS), mental health value, emotional wellbeing, and satisfaction. An online survey method was utilized to reach Romanian patients. Using this procedure, a total of 386 cases were used for the data analysis. Structural equation modeling was utilized as the data analysis method. Our findings reveal that natural/green environment as NBS significantly influences patients' mental health value, emotional wellbeing, and satisfaction, which contributes to an increase in their attachment to the healthcare facility. In addition, the mediating role of mental health value, emotional wellbeing, and satisfaction is uncovered. Our results can help healthcare managers and researchers develop strategies to effectively integrate natural/green features as NBS in the interior spaces of healthcare settings.